Geometry Analysis of Prabumulih Mine Main Road at PT. Kalimantan Prima Persada Jobsite Pelh, West Merapi District, Lahat Regency, South Sumatera - Fariq Dwi Satria Diansa; Mulya Gusman (Journals Mining Engineering : Bina Tambang, 2024)
Coal is a resource consumed by the world as the main ingredient in power generation and the staple material for steel and cement production. Within the Priyamanaya Energi Pit (PELH), which is a mining site, PT Kalimantan Prima Persada, which is a contractor, is involved in the process of coal mining.Within the Priyamanaya Energi Pit (PELH), which is a mining site, PT Kalimantan Prima Persada, which is a contractor, is involved in the process of coal mining. Coal extraction is being carried out at the Priyamanaya Energi Pit (PELH), which is a mining facility owned and operated by PT Kalimantan Prima Persada, a contractor. An alternate path that goes through this ravine is now available for usage by the Prabumulih Road, which was once used by a significant amount of traffic. According to observations made in the field, certain sections of road do not have the optimal road shape. Starting from the Cross Slope, several sectors are not suitable, whose ideal value is 2-5%, but the actual conditions are only around 1.5 2%, there is no water rope, the road width is not ideal where it has a width of less than 25 meters with an ideal value of 25 meters, and there is no Separator (Median), there is Superelevation with an ideal value of 4% but in actual conditions only around 1.4%. However, some parameters are by the actual, such as grade and safety berm. As a result, the road geometry is not ideal, causing the road conditions to be bad, resulting in the conveyance speed not being achieved.